Numerical and experimental exploration towards a 26% efficiency rear-junction n-type silicon solar cell with front local-area and rear full-area polysilicon passivated contacts. (June 2021) - Liu, Zunke; Yang, Zhenhai; Wang, Wei; Yang, Qing; Han, Qingling; Ma, Dian; Cheng, Hao; Lin, Yiran; Zheng, Jingming; Liu, Wei; Liao, Mingdun; Chen, Hui; et al.
Highlight: Rear-junction n-type solar cell with front localized n-type and rear full-area p-type polysilicon contacts is studied. Efficiency of rear-junction solar cell is sensitive to front contact resistivity. Simple modified TLM is developed to measure ρ c of polysilicon contact accurately. ρ c of n-type polysilicon contact reaches ~0.002 Ωcm 2 after 920 °C annealing. Rear-junction n-type solar cell can reach 25.95% with existing technology. Abstract: In this work, structure designs and the corresponding energy loss analysis are conducted to achieve the high-efficiency n-type rear-junction solar cells with polysilicon passivated contact. We focus on the front-side structure design of solar cells, considering that the primary efficiency loss of the conventional n-type polysilicon passivated contact cells with boron-diffusion emitter is from the front side. A well-designed rear-junction solar cell with front localized n-type and rear full-area p-type polysilicon passivated contacts is expected to overcome these problems. However, the efficiency of rear-junction solar cells is sensitive to the front-side electrode contact resistivity. To accurately assess the practically achievable efficiency that the current technology can reach, we develop a simple modified TLM with wet-chemical etching to measure the contact resistivity of the n-type polysilicon contact. This method does not require relatively expensive photolithography and reactive ion etching tools and is easy to be used. When the contact resistivity of the front-side localized n-type polysilicon contact reaches 0.002 Ω·cm 2 with a saturation current density of ~10 fA/cm 2 in the front-side un-diffused area, the efficiency of the rear-junction n-type solar cell is expected to be ~26%, showing its potential for application in mass-production of high-efficiency crystalline silicon solar cells.